The effects of external shocks on the Korean economy: CGE model-based analysis - Hyeok Lee; Yong Kyun Kim (Journal of Economic Structures, 2018)
The trend of low commodity prices looks to continue. Such a trend will affect small open economies that are heavily commodity import dependent, such as the economy of South Korea. Hence, it is of interest to see how the economy would have performed differently with changes in the imported commodity price. In order to systematically investigate this effect, this paper utilizes the Computable General Equilibrium model. In applying the model, maximum entropy estimation approach is used to estimate behavioral parameters for the model. The results of scenario analyses seem to indicate that technology intensity of the industries dictates how differently the given industry will behave with regard to the change in crude oil prices.
Keywords: 330; CGE; External shock; Oil price; Korean economy